2020
DOI: 10.1021/acs.energyfuels.0c01721
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Computational Analysis Exploring the Formation of Caprolactam-Based Deep Eutectic Solvents and Their Applications in Natural Gas Desulfurization

Abstract: Several deep eutectic solvents (DESs) have been recently developed for extraction of hydrogen sulfide from natural gas. Among these newly designed DESs, a combination of caprolactam and tetrabutylammonium halides at a molar ratio of 1:1, as the DESs, has the highest desulfurization efficiencies. In this work, we explored the formation of caprolactam-based DESs using molecular dynamics (MD) simulations and ab initio computations. The results, based on the time average of the equilibrated production run of MD si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…As shown in Figure a, the peak of CPL located at 3207 cm –1 was attributed to the N–H stretching vibration, which shifted to 3277 cm –1 . According to structure optimization by Gaussian, it could be deduced that hydrogen bonds, such as the C–N···H–C and the N–H···Br bonds between CPL and TBAB, were formed. , The hydrogen bonding interaction also caused the shift of the stretching vibration of the C–N bond from 1364 to 1353 cm –1 . In addition, it could be observed that the peak of CO in CPL red-shifted from 1653 to 1648 cm –1 due to the hydrogen bonding interaction between CO and C–H in TBAB.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Figure a, the peak of CPL located at 3207 cm –1 was attributed to the N–H stretching vibration, which shifted to 3277 cm –1 . According to structure optimization by Gaussian, it could be deduced that hydrogen bonds, such as the C–N···H–C and the N–H···Br bonds between CPL and TBAB, were formed. , The hydrogen bonding interaction also caused the shift of the stretching vibration of the C–N bond from 1364 to 1353 cm –1 . In addition, it could be observed that the peak of CO in CPL red-shifted from 1653 to 1648 cm –1 due to the hydrogen bonding interaction between CO and C–H in TBAB.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Parameters are given Antibiotics in DES [ 151 ] 14 Benzene-1,4-diol:Urea Different molar ratios AMBER99 Investigation of DES structure and dynamics and water effect on it [ 371 ] 15 Betaine:Lactic acid (1:1) No name of FF. Parameters are given Investigation of DES structure [ 153 ] 16 Betaine Monohydrate:Glycerol Different molar ratios GAFF/no corrections Extraction of palmitic acid by DES [ 372 ] 17 Betaine Monohydrate:Glycerol (1:2) GAFF/no corrections Investigation of DES structure [ 373 ] 18 Bis(trifluoromethanesulfonyl)imide:Methanesulfonamide Bis(trifluoromethanesulfonyl)imide:Dimethylmethanesulfonamide Different molar ratios OPLS-AA/no corrections Characterization of the transport properties of binary DESs [ 374 ] 19 Caprolactam:Tetrabutylammonium bromide (1:1) Caprolactam:Tetrabutylammonium bromide (1:1) ChCl:Urea (1:2) Methyltriphenylphosphonium bromide:Monoethanolamine (1:6) Gromos54a7, the optimized forcefield parameters were obtained from the Automated Topology Builder (ATB) database Natural Gas Desulfurization using DES [ 375 …”
Section: Table A1mentioning
confidence: 99%
“…114 Moreover, the IL with the lowest Henry's constant has the weakest interaction energy between anion and cation, which would lead to an increase of free volume for H 2 S to occupy and thus improve H 2 S solubility. Amhamed et al 116 RDFs between H 2 S with CH 4 and the components of caprolactam (CPL)-based DES (CPL/TBABr with a molar ratio of 1:1) were computed by Karibayev et al, 117 to explore the interactions within the DES, and to examine the interactions between the DES with H 2 S and CH 4 in natural gas. As shown in Figure 8, the highest peak at a distance of 3.9 Å indicated the strong interaction between the H 2 S molecule and the Br of the DES.…”
Section: Theoretical Studiesmentioning
confidence: 99%
“…RDFs between H 2 S with CH 4 and the components of caprolactam (CPL)-based DES (CPL/TBABr with a molar ratio of 1:1) were computed by Karibayev et al, to explore the interactions within the DES, and to examine the interactions between the DES with H 2 S and CH 4 in natural gas. As shown in Figure , the highest peak at a distance of 3.9 Å indicated the strong interaction between the H 2 S molecule and the Br of the DES.…”
Section: Theoretical Studiesmentioning
confidence: 99%